2016
DOI: 10.4236/gep.2016.46005
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Discriminant for Provenance Characterization and Palaeogeography of Shales from Dahomey Embayment, Southwestern Nigeria

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Discrimination diagrams proposed by Bhatia (1983) and Roser and Korsch (1986) have been traditionally and widely used for decades to obtain tectonic information from sediments/sedimentary rocks deposited in basins (e.g. McCann, 1988;Burnet and Quirk, 2001;Gu et al, 2002;Tijani et al, 2010;Ejeh et al, 2015;Ogala et al, 2015;Ejeh, 2016;Zaid, 2016), although their validity has been questioned (e.g. Winchester and Max, 1989;Shao et al, 2001;Armstrong-Altrin and Verma, 2005;Ryan and Williams, 2007;Borges et al, 2008;Armstrong-Altrin, 2009;Guo et al, 2011;Ghosh et al, 2012;and Zaid, 2012).…”
Section: Plate Tectonic Settingmentioning
confidence: 99%
“…Discrimination diagrams proposed by Bhatia (1983) and Roser and Korsch (1986) have been traditionally and widely used for decades to obtain tectonic information from sediments/sedimentary rocks deposited in basins (e.g. McCann, 1988;Burnet and Quirk, 2001;Gu et al, 2002;Tijani et al, 2010;Ejeh et al, 2015;Ogala et al, 2015;Ejeh, 2016;Zaid, 2016), although their validity has been questioned (e.g. Winchester and Max, 1989;Shao et al, 2001;Armstrong-Altrin and Verma, 2005;Ryan and Williams, 2007;Borges et al, 2008;Armstrong-Altrin, 2009;Guo et al, 2011;Ghosh et al, 2012;and Zaid, 2012).…”
Section: Plate Tectonic Settingmentioning
confidence: 99%
“…Geochemical fingerprints can predict where petroleum, water and other valuable minerals can be found [2]. The use of inorganic geochemical fingerprints for the classification of siliciclastic sediments, provenance, tectonic setting and depositional environment have been carried out by different workers [2][3][4][5][6][7][8][9]. The geochemical study using X-ray fluorescence analysis for the reservoir rocks of Surma Basin in Bangladesh showed that the reservoir rocks are mainly greywacke to lithic arenite and are from quartzose sedimentary provenance which was deposited under active continental margin setting [2].…”
Section: Introductionmentioning
confidence: 99%
“…Classification of Hawkesbury sandstones was achieved by using X-ray fluorescence and the sandstones were classified as quartz arenites with subordinate sublithic arenites [6]. Combined methods of fusion inductively coupled plasma (FUS-ICP) and fusion inductively coupled plasma emission/mass spectrometry (FUS-ICP/MS) were used to determine the tectonic setting of sediments from Dahomey Embayment and passive continental margin tectonic setting was decipher for area [7]. Trace and rare earth element ratios were used to determine the geochemical signatures of some sediment from the Niger Delta Basin and the conclusion was that felsic source rock is the provenance for the sediment from the Agbada Formation [8].…”
Section: Introductionmentioning
confidence: 99%